PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP EMPLOYEE PERFORMANCE DENGAN LEARNING ORGANIZATION SEBAGAI MEDIASI - Herryanto Herryanto; Zuyyina Choirunnisa; Gandi A Yogatama (Universitas Bina Taruna Gorontalo, 2023)
The purpose of this research is to examine the direct influence of transformational leadership on employee performance, as well as the mediating role of the learning organization in public organizations, specifically in Regional Government Agencies. This study employs a quantitative research approach to describe and test the relationships between variables. Using a sample of 100 respondents from employees within the Department of Education and Culture in Belitung Regency, selected through simple random sampling, data were collected using questionnaire distribution techniques. The collected data were processed and analyzed using PLS-SEM. Theresults of this research reveal that transformational leadership has a weak and non-significant influence on employee performance, whereas a strong and significant influence occurs when mediated by the learning organization. Based on the research findings, it can be concluded that the learning organization plays a role in assisting leaders in enhancing performance because within a learning organization environment, employees are provided with opportunities to continuously learn and update their knowledge and skills to adapt to changes.